Pengaruh Konsentrasi Kepemilikan, Profitabilitas, Konservatisme Akuntansi dan Pertumbuhan Penjualan, terhadap Nilai Perusahaan - Putri, Deanti Utami; Chandra, Novrina (Jurnal Ilmiah Poli Bisnis, 2024)
This research discusses the influence of ownership concentration, profitability, accounting conservatism and sales growth on company value. The main objective of this research is to analyze and obtain empirical evidence whether there is an influence of ownership concentration, profitability, accounting conservatism, and sales growth on company value. The ownership concentration variable is measured using the Ownership formula, profitability is measured using the Return of Assets formula, accounting conservatism is measured using the Non-Operating Accrual formula, and sales growth is measured using the sales growth indicator formula. The method used to process data is a quantitative method with data collection techniques using the purposive sampling method. Data processing uses multiple linear regression analysis techniques. The research object is non-cyclical consumer sector companies listed on the Indonesia Stock Exchange (BEI) during the period 2019 to 2022, where from the results of the analysis it was found that there were 27 non-cyclical consumer companies listed on the Indonesian Stock Exchange during 2019 to 2022. Results This research shows that the variables that influence company value include profitability variables and sales growth variables.